The Analysis of the Innovation Consciousness of College Student Entrepreneurs Under the Teaching Concept of Chinese Excellent Traditional Culture - Geng, Bin; Huang, Tianyun; Jiang, Xinsheng; Lin, Nana; Gao, Guangyuan; Fan, Lisha (Frontiers in Psychology, 2021)
The purpose is to analyze the current situation of college student entrepreneurs’ entrepreneurial consciousness, and to explore the role of innovative and entrepreneurial talents in social and economic development. Based on the teaching concept of Chinese excellent traditional culture, first, the relevant theories of innovation and entrepreneurship, as well as the characteristics of entrepreneurial talents in colleges and entrepreneurs are analyzed and elaborated; moreover, the definition of college student entrepreneur is explained; then, from the perspective of entrepreneurial teaching management, entrepreneurial education and place support, the questionnaire method is selected to show the understanding of college students' entrepreneurship; finally, based on Cobb-Douglas, the model before and after the introduction of innovative and entrepreneurial talents is tested and analyzed. Investigation and analysis suggest that most college students have entrepreneurial intention, and 61.5% of them choose to start their own business after having working experience; the relative freedom of time and space is the main factor to attract college students to start their own businesses, accounting for 42.3%; 69.3% of college students think that capital is a restricting factor for entrepreneurship, while 76.2% think that lack of experience is a major restricting factor for entrepreneurship; college students have a certain demand for entrepreneurship training and guidance from the school, especially in the setting of entrepreneurship incubation park and resource pool; the characteristics of entrepreneurship, professional skills and interpersonal resources are more crucial for college students; most college students have a positive cognition of the excellent traditional Chinese teaching concepts; the analysis based on Cobb-Douglas function reveals that the introduction of innovative and entrepreneurial talents can promote economic development. This exploration has a positive effect on the cultivation of college students' awareness of entrepreneurship and innovation, as well as the relationship discussion between the introduction of innovative and entrepreneurial talents and social economy.